Efektivitas Penggunaan Modal Kerja pada PT Sepatu Bata Tbk dan PT Primarindo Asia Infrastructure Tbk Periode 2019-2023 - M. Astri Yulidar Abbas; Safrullah Safrullah; Sri Wahyuti; Ali Mushofa (MAMEN: Jurnal Manajemen, 2025)
This study investigates the effectiveness of working capital utilization at PT Sepatu Bata Tbk (BATA) and PT Primarindo Asia Infrastructure Tbk (BIMA) during the 2019–2023 period. Using a quantitative comparative approach, the research analyzes quarterly financial reports obtained from the Indonesia Stock Exchange. The analysis employs four key ratios: cash turnover, accounts receivable turnover, inventory turnover, and working capital turnover, compared to industry benchmarks. The results reveal that BATA demonstrates superior performance in managing cash and receivables, consistently exceeding the industry standard, while BIMA records lower effectiveness with only sporadic improvements. Both companies, however, perform poorly in inventory management, as indicated by consistently negative turnover values that highlight structural inefficiencies and declining demand in the footwear industry. Working capital turnover also fluctuates considerably: BATA reached extraordinary peaks in 2022–2023 but later recorded negative values, while BIMA persistently showed instability and negative performance after 2021. These findings suggest that effective working capital management is crucial to maintaining liquidity and operational continuity, particularly in industries facing global economic pressures, shifting consumer preferences, and supply chain disruptions. The study contributes to financial management literature by providing empirical evidence on the importance of optimizing working capital strategies to sustain competitiveness in the Indonesian footwear sector.